Personality and safety citizenship: the role of safety motivation and safety knowledge. Issue 1 (January 2020) - Laurent, Julie; Chmiel, Nik; Hansez, Isabelle
Abstract: Safety citizenship behaviors (SCB) have never been classified following the intended beneficiary of these behaviors. The first aim of this study was to examine Hofmann et al. (2003)'s SCB items in an attempt to identify two dimensions: SCB oriented towards individuals (SCB-I) and SCB oriented towards the organization (SCB-O). Further, by drawing on Christian et al. (2009)'s model of safety performance, we examined how distal (i.e. personality) and proximal (i.e. safety motivation and knowledge) person-related factors are associated with these behaviors. Structural equation modelling realized on a sample of 290 workers from a Belgian pharmaceutical company showed that the broader conscientiousness trait was related to both SCB-I and SCB-O, indirectly through safety motivation and knowledge, as would be predicted by Christian et al. In contrast, the altruism facet was directly related to SCB-I only. Results are discussed and practical implications considered. Abstract : Psychology; Conscientiousness; Safety knowledge; Safety motivation; Altruism; Safety citizenship behaviours oriented towards individuals (SCB-I); Safety citizenship behaviours oriented towards organization (SCB-O)